Eumycetoma caused by Fonsecaea sp.: case report of a cat in Costa Rica - Diez-Guevara, Ericka (2025)
Although subcutaneous mycoses are not common, they are more frequent in domestic cats due to behaviors such as burying feces, hunting, and engaging in territorial disputes. However, these pathologies are often underdiagnosed because their clinical signs can be confused with tumoral or bacterial etiologies. This paper reports the first case of eumycetoma caused by Fonsecaea sp. in a cat. In late September 2018, an 8-year-old male mixed-breed feline was treated for a suppurative lesion on the nasal plane, with a recent history of squamous cell carcinoma in the left ear, which had been treated with a conchectomy. During the clinical examination, the cat was found to have a poor body condition score of 2/5. The nasal lesion resulted in sneezing, experiencing pain, and having swollen mandibular lymph nodes. The lesion appeared inflamed and exhibited fistulous characteristics, with black granules and serosanguineous drainage. The cat tested negative for Feline Immunodeficiency Virus and Feline Leukemia Virus, and radiographs of the head revealed bone lysis. Fine-needle aspiration cytology revealed the presence of granular dematiaceous thalli, confirming a diagnosis of eumycetoma. Fonsecaea sp. was identified through mycological culture. The patient was treated with Itraconazole 50 mg PO SID for one month but later developed neurological signs and was euthanized. Due to the recurrent and invasive nature of dark fungi and their poor response to antifungals, a mycological culture is always recommended whenever a mycosis is suspected or confirmed to ensure more effective management of these pathologies.